Examining the Differential Effects of Operating and Investing Cash Flows on Stock Returns: Evidence from an Indonesian Consumer Goods Company - Mishelei Loen; Yuaniko Paramitra (Santoso Academy Network, 2026)
This study investigates the influence of operating and investing cash flows on stock returns at PT Mayora Indah Tbk during the 2014–2022 period. The study is motivated by inconsistent findings regarding the ability of cash flow components to explain stock returns in the Indonesian capital market. While previous studies have reported mixed results, limited evidence exists from an in-depth analysis of a single publicly listed company over an extended observation period. Using a quantitative approach, this research analyzes secondary data obtained from the company’s annual financial statements and stock price information published by the Indonesia Stock Exchange. The sample consists of PT Mayora Indah Tbk observed over nine years, enabling an assessment of the relationship between cash flow information and stock performance. The findings indicate that operating cash flow plays an important role in influencing stock returns because it reflects the company’s ability to generate cash from core business activities and signals financial strength. In contrast, investing cash flow has a more limited effect on stock returns, as investor responses depend on the perceived effectiveness of investment decisions. This study contributes to signaling theory by demonstrating the relevance of operating cash flow in evaluating stock return prospects.